2017
DOI: 10.1186/s12245-017-0157-4
|View full text |Cite
|
Sign up to set email alerts
|

Variation in outpatient emergency department utilization in Texas Medicaid: a state-level framework for finding “superutilizers”

Abstract: BackgroundVery frequent outpatient emergency department (ED) use—so called “superutilization”—at the state level is not well-studied. To address this gap, we examined frequent ED utilization in the largest state Medicaid population to date.MethodsUsing Texas Medicaid (the third largest in the USA) claims data, we examined the variability in expenditures, sociodemographics, comorbidities, and persistence across seven levels of ED utilization/year (i.e., 1, 2, 3–4, 5–6, 7–9, 10–14, and ≥ 15 visits). We classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The size of the high utilizer population varies from 1% to 7% of the overall population for different years and model parameter settings. In terms of population size identified, the proportion is similar to count-based methods [25].
Fig.
…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…The size of the high utilizer population varies from 1% to 7% of the overall population for different years and model parameter settings. In terms of population size identified, the proportion is similar to count-based methods [25].
Fig.
…”
Section: Methodsmentioning
confidence: 85%
“…Inpatient acute care hospital and emergency department (ED) are two important types of health care services. Because inpatient acute care hospital costs are generally an order of magnitude higher than ED costs [25], to better analyze the variations in these two types of services, we stratify the adjustment model by these settings. For this purpose, in each setting, the study population is restricted to those who had nonzero expenditures in the corresponding setting.…”
Section: Methodsmentioning
confidence: 99%
“…There is no consistent definition of super utilizers; however, the lowest common threshold in the literature is patients with four or more ED visits in a 12 month period [ [19] , [20] , [21] ]. These individuals account for a disproportionate number of hospital visits and healthcare costs [ 19 , [21] , [22] , [23] ]. Numerous studies have examined patient characteristics [ 19 , [21] , [22] , [23] , [24] , [25] ], patient complaints [ 24 ], super utilizer behavior classification [ 20 ], and appropriateness of care for these patients [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…HCHN patients have shown a high degree of persistence in medical expenditures reflected in administrative claims data [ 2 , 13 ], although some recent studies have concluded that the high utilization may be temporary and not persistent [ 14 ]. The purpose of this study is to better understand these temporal patterns and to apply machine learning-based models to predict expenditures.…”
Section: Introductionmentioning
confidence: 99%